Neoadjuvant Weekly Paclitaxel-Carboplatin Is Effective in Stage I–II Cervical Cancer. Issue 6 (1st July 2017) - Salihi, Rawand; Leunen, Karin; Moerman, Philippe; Amant, Frédéric; Neven, Patrick; Vergote, Ignace
Abstract : Objective: Neoadjuvant chemotherapy (NACT) followed by surgery in cervical cancer is widely studied with paclitaxel-ifosfamide-cisplatinum 3 weekly (TIP). Although the response rates with TIP are high, the toxicity is substantial. Therefore, this study evaluates dose-dense paclitaxel-carboplatin (TC) as an alternative. Methods: In this prospective phase 2 study trial, we included 36 patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB1 to IIB cervical cancer, who received 9 weeks' NACT dose-dense TC (median weekly dose paclitaxel 60 mg/m 2, carboplatinum area under the curve 2.7). Radiological response was evaluated by RECIST (Response Evaluation Criteria in Solid Tumors). Optimal pathologic response (OPT) was defined as complete disappearance of tumor (complete response [CR]) or residual disease with less than 3-mm stromal invasion (PR1). Suboptimal pathologic response consisted of persistent residual disease with more than 3-mm stromal invasion (PR2). Results: Nine patients had a FIGO stage IB1 (25%), 7 had stage IB2(19%), 3 had stage IIA (8%), and 17 had stage IIB disease (47%). Evaluation by magnetic resonance imaging after NACT showed 32 RECIST responses (89%) (CR in 11, PR in 21). Patients who were inoperable had insufficient reduction of the tumor to be operable (4 patients), progressive disease (1 patient), or stable disease (1 patient). Thirty patients were suitable for surgery after NACT. Pathology showed OPT in 50% (CR in 10, PR1 in 5). Thirteen patients had pathologic lymph nodes on radiological evaluation before start of chemotherapy. After chemotherapy, the lymph nodes were negative in 6 (47%) of these patients (pathologic complete remission). Postoperative chemoradiotherapy was administered in 11 patients (2 because of close resection margins, 5 because of metastatic lymph node after surgery, 2 because of close resection margins and metastatic lymph nodes after surgery, and 1 tumor >4 cm after NACT). Hematologic toxicity was acceptable with no febrile neutropenia and a low nonhematologic toxicity. The estimated 5-year overall survival was 70.8%. Conclusions: Neoadjuvant TC dose-dense in cervical carcinoma has a high response rate, comparable with TIP, and an acceptable toxicity.